Peranan Aqidah Islam dalam Pembentukan Religiusitas Remaja di Desa Tembung Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Sormin, Tiurma Indah; Nasution, Hasan Bakti; Harahap, Salahuddin (Lembaga Yasin AlSys, 2024)
The most important and frequent spiritual component of people is called aqidah, or belief, which instructs physical members of the human race to perform specific tasks. Good faith will lead to good deeds from people, but bad faith will lead to bad deeds from people as well. The purpose of this study is to determine how Islamic Aqidah influences the development of teenage religiosity in Tembung Village, Percut Sei Tuan District, Deli Serdang Regency. Research from libraries and the field were combined for this study. The two approaches used in this study are the sociological approach (sociological approach) and the Islamic Aqidah method (Islamic theological approach). In Tembung village, the formation of teenage religiosity is greatly influenced by the Islamic faith. The standard of a person's religion is established by aqidah. Reluctant learners of aqeedah frequently make mistakes and introduce additional issues into their life. as a manual for life that will help you distinguish between right and wrong, guard against making mistakes, cultivate a sense of adoration for Allah SWT, soothe your soul, and comprehend and abide by the sunnah.